A qualitative analysis of aspects of treatment that adolescents with anorexia identify as helpful. (30th April 2016) - Zaitsoff, Shannon; Pullmer, Rachelle; Menna, Rosanne; Geller, Josie
Abstract: This study aimed to identify aspects of treatment that adolescents with anorexia nervosa (AN) believe are helpful or unhelpful. Adolescent females receiving treatment for AN or subthreshold AN ( n =21) were prompted during semi-structured interviews to generate responses to open-ended questions on what they felt would be most helpful or unhelpful in treating adolescents with eating disorders. Eight codes were developed and the two most frequently endorsed categories were (1) Alliance, where the therapist demonstrates clinical expertise and also expresses interest in the patient ( n =21, 100.0%), and (2) Client Involvement in treatment ( n =16, 76.2%). These top two categories were shared by participants with AN versus subthreshold AN and participants with high versus low readiness to change their dietary restriction behaviours. Development of the coding scheme and sample participant responses will be discussed. The integration of identified factors into empirically supported treatments for adolescent AN, such as Family-based Treatment, will be considered. This study provides initial information regarding aspects of treatment that adolescents identify as most helpful or unhelpful in their treatment. Highlights: Qualitative responses on helpful/unhelpful aspects of treatment from adolescent females with AN were coded into categories. The two most frequently endorsed categories were (1) Alliance and (2) Client Involvement in treatment. The top categories were shared among youth with varying symptom severity and readiness to change restriction behaviours.